H2-poor bio-syngas in Fischer-Tropsch synthesis over un-promoted and rhenium promoted alumina-supported cobalt catalysts: Effect of water addition - Dewi Tristantini; Borje Gevert (ASEAN Journal of Chemical Engineering, 2009)
The effect of water addition on Fischer-Tropsch synthesis (FTS) over 12%Co/Al2O3 and 12%Co-0.5%Re/Al2O3 catalysts was investigated in a fixed bed reactor with model mixtures of biomass-derived syngas (bio-syngas). The bio-syngas model mixtures consist of H2 and CO of different molar H2/CO-ratios (1.0, 1.5 and 2.1). The FT-reaction requires a H2/CO molar ratio of approximately 2.1 above the catalyst surface. For the ratios lower than 2.1, an in situ water-gas shift (WGS) activity is desired in order to increase the H2/CO-ratio. However, the studied catalysts had quite low WGS activities. The addition of water slightly increased the WGS activity for all types of bio-syngases and for both catalysts. The highest WGS activity was found for the un-promoted Co-catalyst at the inlet H2/CO-ratio = 1.0. Water addition also results in an increase in selectivity to C5+ and a decrease in selectivity to CH4 . Interestingly, for both of catalysts the selectivity to C5+ and CH4 were rather similar for inlet H2/CO-ratios of 2.1 and 1.5, while the highest selectivity to C5+ and the lowest selectivity to CH4 were also found for the inlet ratio = 1.0. All catalysts were deactivated by water addition but the catalyst activity is partly recovered in H2/CO-ratio inlets = 1.0 and 1.5. The Co/Al2O3 was affected by water more severely in H2/CO ratios = 2.1. The Re-promoted Co catalyst was considerably more active and selective to longer hydrocarbons than the un- promoted one. The conclusion of this study is that in order to utilize the advantages of a bio-syngas with a low H2 content (higher selectivity to C5+ , lower selectivity to CH4, no WGS-unit needed prior to FT-reactor), the catalyst must possess a much higher WGS activity than the ones studied.